Gambaran Pembiayaan Farmasi di Rumah Sakit Pemerintah dengan Pengelolaan BLU/BLUD - Lukman Prayitno; Selma Siahaan (Buletin Penelitian Sistem Kesehatan, 2019)
Pharmacy costs are one of the components that absorb the largest costs from the hospital's health budget. At present, there is still little information and data on the percentage of pharmaceutical costs to the costs of medical devices and non-medical devices. It is very useful in making financial planning. It can illustrate of pharmaceutical financing against other operational costs in hospitals, as financial planning, as scientific evidence for improving drug policy. This research was an analysis on the Indonesia Health Financing Survey data in the referral health care Facilities (FKRTL) in 2016. Data from 84 hospitals in 3 regions. The details were 9 class A hospitals, 37 class B hospitals, 38 class C hospitals. The analysis used a descriptive statistical approach. Pharmacy costs in 3 types of hospitals were 169.07 Billion, 23.66 Billion, 10.79 Billion. The percentage of the proportion of pharmaceutical costs to the cost of non-medical equipment in 3 types of hospitals is 1073.05%, 665.42%, 292.29%. The proportion of pharmaceutical costs to the cost of medical devices in 3 types of hospitals is 208.12%, 172.20%, 148.96%. In all types of hospitals the total pharmaceutical costs are greater than the costs of medical equipment and non-medical equipment costs. The proportion of pharmaceutical costs to the costs of non-medical devices and medical devices is high. This is due to the depreciation of the cost of medical devices and non-medical devices while the pharmaceutical costs always increase in price from the previous year. Abstrak Biaya farmasi merupakan salah satu komponen yang menyerap biaya terbesar dari anggaran kesehatan Rumah Sakit. Saat ini masih sedikit informasi dan data mengenai prosentase biaya farmasi terhadap biaya alat medis dan alat non-medis. Prosentase biaya di rumah sakit sangat bermanfaat dalam membuat perencanaan pembiayaan. Data penelitian sebagai gambaran pembiayaan farmasi terhadap biaya operasional lain di rumah sakit, sebagai perencanaan pembiayaan, sebagai bukti ilmiah untuk penyempurnaan kebijakan obat. Data riset merupakan analisis lanjut hasil Riset Pembiayaan Kesehatan Fasilitas Kesehatan Rawat Tingkat Lanjut (FKRTL) Tahun 2016. Data dari 84 rumah sakit yang di 3 regional. Dengan rincian adalah 9 rumah sakit kelas A, 37 rumah sakit kelas B, 38 rumah sakit kelas C. Data riset dimasukkan dalam dumy tabel untuk analisa lanjut. Analisis menggunakan pendekatan kuantitatif statistik diskriptif. Biaya farmasi pada 3 tipe RS masing-masing sebesar 169,07 Milyard, 23,66 Milyard, 10,79 Milyard. Prosentase proporsi biaya farmasi terhadap biaya alat non medis pada 3 tipe RS adalah 1073,05%, 665,42%, 292,29%. Prosentase proporsi biaya farmasi terhadap biaya alat medis pada 3 tipe RS adalah 208,12%, 172,20%, 148,96%. Di semua tipe RS total biaya farmasi lebih besar dibanding biaya alat medis dan biaya alat non medis. Prosentase proporsi biaya farmasi terhadap biaya alat non medis dan alat medis menjadi tinggi. Hal ini disebabkan terjadi penyusutan terhadap biaya alat medis dan alat non medis sedangkan biaya farmasi selalu terjadi peningkatan harga dari tahun sebelumnya.